2002
DOI: 10.1590/s0004-282x2002000100024
|View full text |Cite
|
Sign up to set email alerts
|

Displasia tanatofórica: Relato de dois casos com estudo neuropatológico

Abstract: RESUMO -O relato tem como objetivo apresentar dois casos de displasia tanatofórica (DT), um caso do tipo I e outro do tipo II, com especial atenção ao sistema nervoso central. No caso compatível com DT tipo I foram observados macrocefalia, tórax estreito, hipoplasia pulmonar acentuada, abdome protuberante. Exames radiológicos revelaram platispondilia e ossos curtos encurvados com achatamento e fusão metafisária. No caso compatível com DT tipo II foram observados megaencefalia, fenda palatina, membros curtos e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Miller et al [11] have stated that it is important to assess the brains of fetuses with suspected thanatophoric dwarfism because the presence of associated brain malformations can assist in the antenatal diagnosis and accurate counselling of patients. Noronha et al [12] in report of 2 cases of thanatophoric dysplasia have reported that both cases revealed temporal lobe polymicrogyria, abnormalities of the hippocampus and heterotopic neuroglial tissue within the meninges.…”
Section: Discussionmentioning
confidence: 99%
“…Miller et al [11] have stated that it is important to assess the brains of fetuses with suspected thanatophoric dwarfism because the presence of associated brain malformations can assist in the antenatal diagnosis and accurate counselling of patients. Noronha et al [12] in report of 2 cases of thanatophoric dysplasia have reported that both cases revealed temporal lobe polymicrogyria, abnormalities of the hippocampus and heterotopic neuroglial tissue within the meninges.…”
Section: Discussionmentioning
confidence: 99%
“…Thanatophoric dysplasia consists in a lethal congenital disease related to genetic mutations with bone and neural repercussions and it is characterized by bone dysplasia with shortening of the limbs, hypo-plastic ribcage and macrocephaly. Its approximate incidence in the population is of 1 to 35,000-50,000 births, being a disease with low rate of recurrence in following pregnancies 14 . Most cases are stillborn and those who are born alive die shortly after birth.…”
Section: Congenital Anomalies Incompatible With Extrauterine Lifementioning
confidence: 99%